Use of the Wilkinson Catalyst for the ortho‐CH Heteroarylation of Aromatic Amines: Facile Access to Highly Extended π‐Conjugated Heteroacenes for Organic Semiconductors1. Issue 45 (12th September 2014) - Huang, Yumin; Wu, Di; Huang, Jingsheng; Guo, Qiang; Li, Juan; You, Jingsong
Abstract An unprecedented catalytic system composed of the Wilkinson catalyst [Rh(PPh3)3Cl] and CF3COOH enabled the highly regioselective cross‐coupling of aromatic amines with a variety of heteroarenes through dual CH bond cleavage. This protocol provided a facile and rapid route from readily available substrates to (2‐aminophenyl)heteroaryl compounds, which may be conveniently transformed into highly extended π‐conjugated heteroacenes. The experimental studies and calculations showed that thianaphtheno[3, 2‐b]indoles have large HOMO–LUMO energy gaps and low‐lying HOMO levels, and could therefore potentially be high‐performance organic semiconductors. Herein we report the first use of a rhodium(I) catalyst for oxidative CH/CH coupling reactions. The current innovative catalyst system is much less expensive than [RhCp*Cl2]2/AgSbF6 and could open the door for the application of this approach to other types of CH activation processes.